Інформаційні технології при розв'язанні задач в системі екологічного управління - Ємельянова, Дар'я Ігорівна; Козуля, Марія Михайлівна; Козуля, Тетяна Володимирівна (Харківський національний університет радіоелектроніки, 2013)
Informational and software support grounds basis of ecological compatibility estimation method is given in the article and is based upon probabilistic entropic risk analysis for solving ecological security problems at the level of territorial object systems and identify factors that are responsible for the degree of manifestation of the disease and to determine the state of human health
Keywords: екологічна оцінка; природно-техногенні комплекси; промислова екологія; математична модель; моніторинг